(untitled) (Innovative professional education, 2022)
Diploma design is considered as the final stage of training and the final form of monitoring the training of programmer specialists. During the diploma project, future programmers go through the entire life cycle of software development according to their qualifications. This ensures a deep and systematic examination of students’ readiness for professional activity.